The rolB‐transgenic Nicotiana tabacum plants exhibit upregulated ARF7 and ARF19 gene expression. (18th June 2022) - Bose, Rahul; Sengupta, Mainak; Basu, Debabrata; Jha, Sumita
Abstract: Agrobacterium rhizogenes root oncogenic locus B ( rolB ) is known to induce hairy roots along with triggering several physiological and morphological changes when present as a transgene. However, it is still unknown how this gene triggers these changes within the plant system. In this study, the effect of rolB in‐planta, when present as a transgene, was assessed on the gene expression levels of auxin response factors ( ARF s)—transcription factors which are key players in auxin‐mediated responses. The goal was to uncover Auxin/ ARF ‐driven transcriptional networks potentially active and working selectively, if any, in rolB transgenic background, which might potentially be associated with hairy root development. Hence, the approach involved establishing rolB ‐transgenic Nicotiana tabacum plants, selecting ARF s (Nt ARF s) for context‐relevance using bioinformatics followed by gene expression profiling. It was observed that out of the chosen Nt ARF s, Nt ARF7 and Nt ARF19 exhibited a consistent pattern of gene upregulation across organ types. In order to understand the significance of these selective gene upregulation, ontology‐based transcriptional network maps of the differentially and nondifferentially expressed ARF s were constructed, guided by co‐expression databases. The network maps suggested that Nt ARF7 ‐Nt ARF19 might have major deterministic, underappreciated roles to play in root development in a rolB ‐transgenic background—as observed by higher number of "root‐related" biological processes present as nodes compared to network maps for similarly constructed other non‐differentially expressed ARF s. Based on the inferences drawn, it is hypothesized that rolB, when present as a transgene, might drive hairy root development by selective induction of Nt ARF7 and Nt ARF19, suggesting a functional link between the two, leading to the specialized and characteristic rolB ‐associated traits. Significance statement: In this study, it was observed that Nt ARF7 and Nt ARF19 are upregulated in rolB ‐transgenic Nicotiana tabacum plants. To understand their potential relevance, Gene Ontology‐based transcriptional network maps for differentially and nondifferentially expressed ARF s were constructed. Higher number of "root‐related" biological processes were observed for differentially upregulated ARF s as compared with nondifferentially expressed ARF s. Based on the inferences, the existence of a functional link was postulated between rolB and auxin via Nt ARF7 ‐Nt ARF19 leading to the characteristic rolB ‐associated hairy root development in rolB ‐transgenic background.